Jordan calls on PXP to end plans to drill for oil off Santa Barbara coast after Governor drops support Accident in Gulf proves that state-of-the art technology not good enough to prevent massive spills - Jordan, Susan (Susan Jordan)
Newsletter from Susan Jordan to her supporters about an article regarding her opposition for Texas's PXP to drill of the California coast after their massive oil spill that occurred 40 miles of the Louisiana coast. California Governor, Arnold Schwarzenegger also is against PXP drilling plans.